Albania's Entities and Environmental Accounting: Current Public Disclosure and the Reality Behind Closed Doors - Florinda Zherri; Flutura Kalemi (European Scientific Journal, ESJ, 2025)
Environmental accounting (EA) has become an essential tool for incorporating environmental costs and performance into corporate reporting and decision-making. This paper analyzes the status of EA in Albania, a developing economy and EU candidate, by evaluating the public disclosure of environmental information and the internal practices of EA within enterprises. A content analysis was performed on the websites and financial reports of 100 big Albanian enterprises, in conjunction with a structured survey of 71 managers. Results indicate a substantial disparity between outward reporting and internal practices. Public environmental disclosures are scant; only a limited number of corporations release quantitative or financial environmental data, and nearly none produce independent sustainability reports, indicating a "gray" reporting environment. Survey results reveal that approximately one-third of organizations have initiated internal enterprise architecture practices or sustainability initiatives, albeit without external communication. Significant obstacles impeding wider implementation of Environmental Accounting (EA) encompass constrained financial resources, absence of regulatory mandates, inadequate stakeholder pressure, and minimal awareness or proficiency in sustainable accounting, literature indicated to be issues prevalent in poor nations. Analyzing the results via stakeholder, legitimacy, and institutional theories indicates that the lack of external pressures and obligatory frameworks has resulted in complacency in disclosure, notwithstanding increasing internal awareness. The research underscores an immediate necessity for enhanced regulatory frameworks, capacity development, and stakeholder involvement in Albania. In aligning with the EU’s CSRD (2022) and global reporting requirements, it is imperative to bridge the divide between public reporting and private practice to enhance corporate transparency and accountability.